Exploring alternative preschool education methods in Georgia: Enhancing accessibility - N. Kitoshvili (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
This study is relevant as it examines public-private partnerships in early childhood education in Georgia, seeking solutions to the significant educational challenges common to post-Soviet regions. It assesses the suitability of alternative educational models in a society that is still struggling with the infrastructural legacy of the Soviet past, providing valuable recommendations for policy reforms needed to expand access to and improve the quality of preschool education. The purpose of the study was to assess the readiness of Georgian society to implement alternative educational practices. Drawing upon the experiences of post-Soviet nations, alongside international insights and local perspectives, the study aims to provide comprehensive insights into the feasibility and effectiveness of alternative models in Georgia. Employing a mixed-methods approach encompassing qualitative interviews, surveys, and data analysis, the research examines the strengths, challenges, and implementation prospects of various alternative models within the unique socio-economic and cultural context of post-Soviet Georgia. Early childhood education in post-Soviet and similar countries confronts common challenges in access and quality, despite varied policies, with efforts such as legislation and public-private partnerships aimed at addressing financial and geographical barriers. Persistent disparities in preschool systems across the region, as illustrated by reform initiatives and staffing issues in Georgia, highlight the need for continuous reforms. These factors underscore the importance of sustained policy efforts to support comprehensive and effective early learning environments. The results underscore a compelling need for alternative education avenues in Georgia, particularly in regions facing infrastructural and geographical barriers similar to those experienced in other post-Soviet nations. While highlighting the potential benefits of public-private partnerships models, the study also identifies key challenges that need to be addressed to ensure their successful implementation within the post-Soviet context. The practical value of this study extends to policymakers, educators, and communities across post-Soviet countries with similar educational challenges. By advocating for legislative reforms to incorporate alternative approaches, this research contributes to ongoing efforts to strengthen preschool education and promote inclusivity in post-Soviet Georgia and beyond